The design effectivity of burger machine's van outlets - Fernandez, Eugenio S.J; Florendo Raquel B. (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis(BID)--University of the Philippines Diliman
Keywords: Store decoration; Design, Decorative